Assessing the need for management and leadership training in Dentistry in South Africa - Van der Berg-Cloete, S.E. (University of Pretoria, 2018)
The main aim of this study was to assess the need for management and leadership training in dentistry in South Africa (SA). The study also explored stakeholders’ opinion about the most important non-clinical skills to teach dental students and how management and leadership training could best be developed and implemented in dentistry in SA. The design of the study was a qualitative research to understand the participants’ perceptions of leadership and management training. The sample included fourteen senior managers in the dental environment as well as eleven recently qualified dentists in South Africa. One-on-one and telephonic interviews were conducted. Interviews were recorded and data were entered into a Word document and analysed. All ethical requirements were addressed. The study was voluntary and participants signed a consent form to participate in the research. The key findings of the study confirmed that participants were negative about dentistry in SA and agreed that strong leadership was necessary. Management and leadership training in dentistry in SA was therefore seen as utmost important. Participants also agreed that the training should start in the undergraduate level and follow through to the postgraduate level. The results of this study provides valuable information about the need for management and leadership training in dentistry and how it best could be delivered in the South African context.